Desensitizing the autonomic nervous system to mitigate anti-GD2 monoclonal antibody side effects - Mora, Jaume; Climent, Alejandra; Roldán, Mònica; Flores, Marta Cecilia; Varo, Amalia; Perez-Jaume, Sara; Jou, Cristina; Celma, Mónica S.; Lazaro, Juan José; Cheung, Irene; Castañeda, Alicia; Gorostegui, Maite; et al. (Frontiers in Oncology, 2024)
Background: anti-GD2 monoclonal antibodies (mAbs) have shown to improve the overall survival of patients with high-risk neuroblastoma (HR-NB). Serious adverse events (AEs), including pain, within hours of antibody infusion, have limited the development of these therapies. In this study, we provide evidence of Autonomic Nervous System (ANS) activation as the mechanism to explain the main side effects of anti-GD2 mAbs. Methods: through confocal microscopy and computational super-resolution microscopy experiments we explored GD2 expression in postnatal nerves of infants. In patients we assessed the ANS using the Sympathetic Skin Response (SSR) test. To exploit tachyphylaxis, a novel infusion protocol (the Step-Up) was mathematically modelled and tested. Results: through confocal microscopy, GD2 expression is clearly visible in the perineurium surrounding the nuclei of nerve cells. By computational super-resolution microscopy experiments we showed the selective expression of GD2 on the cell membranes of human Schwann cells in peripheral nerves (PNs) significantly lower than on NB. In patients, changes in the SSR were observed 4 minutes into the anti-GD2 mAb naxitamab infusion. SSR latency quickly shortened followed by gradual decrease in the amplitude before disappearance. SSR response did not recover for 24 hours consistent with tachyphylaxis and absence of side effects in the clinic. The Step-Up protocol dissociated on-target off-tumor side effects while maintaining serum drug exposure. Conclusions: we provide first evidence of the ANS as the principal non-tumor target of anti-GD2 mAbs in humans. We describe the development and modeling of the Step-Up protocol exploiting the tachyphylaxis phenomenon we demonstrate in patients using the SSR test.